A New Defect‐Rich CoGa Layered Double Hydroxide as Efficient and Stable Oxygen Evolution Electrocatalyst. Issue 2 (27th September 2018) - Zhang, Jie; Dong, Chaoqun; Wang, Zhenbin; Gao, Hui; Niu, Jiazheng; Peng, Zhangquan; Zhang, Zhonghua
Abstract: Developing highly efficient and earth‐abundant electrocatalysts is urgent for oxygen evolution reaction (OER), and layered double hydroxides (LDHs) show great potentials as advanced electrocatalysts toward OER. However, the catalytic activity of LDHs is normally limited by their poor electronic conductivity and low electrochemical active areas. Herein, a novel sputtering–painting–alloying–dealloying strategy is reported to synthesize CoGa LDH anchored on stainless steel mesh (CoGa LDH/stainless steel mesh, SSM), in which abundant oxygen vacancies are introduced into the ultrathin CoGa LDH nanosheets. Owing to the unique painting‐like operation, the nanosheet‐decorated CoGa LDH/SSM electrode can be fabricated on a large scale (8 × 8 cm 2 for instance), and possesses excellent flexibility and self‐supported feature. Free of any conducting/binder agents, the CoGa LDH/SSM electrode shows excellent electrocatalytic activity toward OER in an alkaline solution (low overpotential of 258 mV @ 10 mA cm −2, small Tafel slope of 34.1 mV dec −1, long‐term stability of 70 h), which is superior to that of state‐of‐the‐art Co‐based electrocatalysts. More importantly, the electrode needs only an overpotential of 198 mV to reach 10 mA cm −2 at 335 K. The OER performance of CoGa LDH/SSM can be rationalized by numerous oxygen vacancies, ultrathin nanosheet morphology, self‐supported nature, and low activation energy barrier. Abstract : The flexible self‐supported CoGa layered double hydroxide (LDH) anchored on stainless steel mesh (SSM) is fabricated by a novel sputtering–painting–alloying–dealloying strategy. The CoGa LDH/SSM electrode shows excellent electrocatalytic activity toward oxygen evolution reaction (OER) in an alkaline solution. And the high OER performance can be rationalized by numerous oxygen vacancies, ultrathin nanosheet morphology, self‐supported nature, and low activation energy barrier.